Identification of vitronectin as a potential non-invasive biomarker of metastatic breast cancer using a label-free LC–MS/MS approach - Roopali Roy; Elisa M. Schunkert; Petra Olivova; Martin Gilar; Scott Geromanos; Guo-Zhong Li; John Gebler; Adelle Dagher; Andrew El-Hayek; Rama Aldakhlallah; Steven J. Staffa; David Zurakowski; et al. (Breast Cancer Research)
Abstract Background Breast cancer (BC) is a complex heterogenous disease that is a leading cause of death in women. For patients with early stage disease following primary BC therapy, approximately 30% will develop metastatic BC (MBC). The median survival of MBC patients is ~ 2–3 yr. While the early detection and monitoring of BC progression have improved prognosis and reduced BC-related mortality, there is a lack of long-term surveillance strategies for monitoring patients for recurrence of MBC. The aim of our study was to identify non-invasive urinary biomarkers for detection and monitoring of MBC. Methods We have conducted a comparative label-free LC–MS/MS analysis of the urinary proteome of patients with MBC and healthy age-matched, sex-matched controls (HC). A hybrid quadrupole time of flight (Q-Tof™) mass spectrometer was used for urine analysis via liquid chromatography (LC) with tandem mass spectrometry (MS/MS). Retrospective analysis of urine samples from MBC and locally invasive breast cancer (IBC) patients as well as HC was conducted. Diagnostic accuracies of candidate markers were validated using independent training and validation sets according to the REMARK criteria. Results Using this approach, we have identified 212 urinary proteins of which 83 and 25 were unique to the MBC and HC groups, respectively. Upregulated proteins in the MBC cohort were associated with angiogenesis, Ca2+ homeostasis, apoptosis, proteolysis, extracellular matrix regulation, cell adhesion and protein synthesis pathways. A specific non-invasive metastasis signature comprised of candidate biomarkers (urinary CALB1, S100A8, ZAG, VTN and TN) were validated and analyzed via monospecific ELISA assays. Urinary vitronectin (uVTN) levels correlated with disease status and were significantly higher in samples from MBC compared to those from IBC patients and HC. uVTN alone (cutoff > 500 ng/ml) could discriminate between HC and MBC groups (AUC = 0.782, P < 0.001). Longitudinal analysis of samples from MBC patients indicated a strong correlation between uVTN levels and disease status. Conclusions Our findings suggest that uVTN is a promising and non-invasive biomarker for the diagnosis and monitoring of MBC. While future validation in larger cohorts should be done, these results identify a novel urinary protein that represents the first non-invasive diagnostic test for monitoring BC progression and recurrence.